2021
DOI: 10.1115/1.4052906
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability-Based Formulation for Simulation-Based Control Co-Design Using Generalized Polynomial Chaos Expansion

Abstract: Combined plant and control design (control co-design, or CCD) methods are often used during product development to address the synergistic coupling between the plant and control parts of a dynamic system. Recently, a few studies have started applying CCD to stochastic dynamic systems. In their most rigorous approach, reliability-based design optimization (RBDO) principles have been used to ensure solution feasibility under uncertainty. However, since existing reliability-based CCD (RBCCD) algorithms use all-at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this section, we start by discussing the optimal control structures under uncertainties in UCCD problems. These structures attempt to answer inherently different questions and have been used in separate studies in the literature [20,[25][26][27][28][29][30][31][32][33]. While these structures have a significant impact on the problem implementation and its associated solution, they have not been collectively discussed in the literature to the best of the authors' knowledge.…”
Section: Uccd Implementationmentioning
confidence: 99%
“…In this section, we start by discussing the optimal control structures under uncertainties in UCCD problems. These structures attempt to answer inherently different questions and have been used in separate studies in the literature [20,[25][26][27][28][29][30][31][32][33]. While these structures have a significant impact on the problem implementation and its associated solution, they have not been collectively discussed in the literature to the best of the authors' knowledge.…”
Section: Uccd Implementationmentioning
confidence: 99%
“…Zhang et al 26 suggested a single-loop framework for RB-CCD by incorporating the approximate reliability information of random physical design into the deterministic optimization. Behtash and Alexander-Ramos 27 suggested a reliability-based formulation for simulation-based control co-design using a combination of generalized Polynomial Chaos expansion and Monte Carlo simulation. The above achievements are pioneering efforts in the field of RB-CCD and have been achieved in both theoretical analysis and engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…And Ref. 27 applied Monte Carlo simulation to the generalized polynomial chaos expansion of the probabilistic constraints according to the additional original system simulations. Hence, it is inevitable that the existing RB-CCD methods consume numerous computational resources to perform the time-consuming system simulations when encountering the RB-CCD problem in the sophisticated dynamic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation